Journal of Shipping and Trade - Lai, Kee-Hung.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Journal of Shipping and Trade (JST) is an open access, multi-disciplinary publication that focuses both on business & management, as well as transportation-related fields. JST aims to promote practices in shipping and to improve the management of global trade activities. Towards achieving these objectives, JST provides a vehicle to facilitate professionals, academics, researchers, and policy makers in the field to disseminate information and to learn from one another$1 (Bs work. As a scholarly journal emphasizing shipping and trade related studies and research, JST plays a key role in establishing communication links among global shipping and trade researchers. JST also aims to contribute to current and emerging issues in shipping and trade as raised by global and regional public bodies (such as the World Bank and OECD) and major market players. JST considers papers covering shipping economics, trade and economic development, transportation management, global port management, regional studies, environmental management in shipping and trade, business model development, as well as other related topics.s
Keywords: Business; Business logistics; Globalization; Markets; Trade; Commerce; Business and Management; Trade; Logistics; Emerging Markets/Globalization.